‘Priming’ protects Piper nigrum L. from Phytophthora capsici through reinforcement of phenylpropanoid pathway and possible enhancement of Piperine biosynthesis - Indu, M.; Meera, B.; Sivakumar, KC.; Mahadevan, Chidambareswaren; Shafi, K Mohammed; Nagarathnam, B.; Sowdhamini, Ramanathan; Sakuntala, Manjula (Frontiers in Plant Science, 2022)
Piper nigrum L. (black pepper), a woody perennial spice crop indigenous to India is positioned at the phylogenetically unique basal lineage of angiosperms. Cultivation of this major spice crop is constrained by rampant fungal and viral infections leading to a lack of disease-free planting material. The major disease that poses severe threat to P. nigrum plantations and nurseries is ‘quick wilt’ caused by the oomycete Phytophthora capsici, which affects the leaf, stem, spike, collar and root. In this paper, we report the consequence of priming in modulating Piper nigrum defense against Phytophthora capsici. Glycol Chitosan (GC) was used to infiltrate detached leaves of mature P. nigrum plants. It was observed that pre-treatment of GC for 24h resulted in significant reduction of disease symptoms in infected leaves, as evidenced by the marked decrease in the size of lesions, and also delayed the appearance of symptoms up to 72 hpi. Experiments repeated in P. nigrum seedlings under controlled growth conditions indicate that delayed disease symptoms of GC pre-treated leaves do not spread to healthy uninfiltrated leaves suggesting a priming-associated systemic defense response. An ROS-mediated manifestation of Hypersensitive Response (HR) induced by Chitosan was also evident in pre-treated leaves. A corresponding visual indication of increased lignification was observed, which correlated with an enhanced lignin content of GC-treated leaves. Enhanced callose deposition was also apparent in GC-infiltrated leaves, establishing a stimulatory effect of GC in triggering HR through ROS production, enhanced lignification and callose deposition. Key genes of the core phenyl propanoid and isoprenoid pathways along with major defense signalling pathway genes of P. nigrum including pathogenesis-related genes and hormone signalling genes showed significant transcript enrichment consequential to GC treatment. A significant quantitative enhancement in Piperine content was evident in GC-infiltrated leaves. This is the first report that provides strong molecular evidence endorsing the twofold advantage of defense priming in P. nigrum by improving crop protection with a concomitant enhancement in Piperine biosynthesis. The systemic nature of priming on disease protection was established through experiments conducted in infiltrated rooted cuttings monitored for 30 days after disease infection.